Lateral flow assay for carbohydrate antigen 19-9 in whole blood by using magnetized carbon nanotubes - Huang, Yan (Mikrochim Acta, 2017)
The authors describe a rapid, low-cost and sensitive approach for the determination of carbohydrate antigen 19-9 (CA 19-9) in whole blood by using magnetized carbon nanotube (MCNT) and lateral flow strip biosensor (LFSB). MCNTs were synthesized by depositing magnetite (Fe(3)O(4)) nanoparticles on multiwalled carbon nanotube (CNT) via co-precipitation of ferric and ferrous ions within a dispersion of shortened multiwalled CNTs. Antibody against CA 19-9 (Ab(1)) was covalently immobilized on the MCNTs and were used to capture CA 19-9 in blood. After magnetic separation, the formed MCNT-Ab(1)-CA 19-9 complexes are applied to the LFSB, in which a capture antibody (Ab(2)) and a secondary antibody (Ab(3)) are immobilized on the test zone and control zone of the LFSB, respectively. The captured MCNTs on the test zone and control zone are producing characteristic brown bands, and this enables CA 19-9 to be visually detected. Quantitation is accomplished by reading the intensities of the bands with a portable strip reader. Under optimized conditions, the assay has a detection limit as low as 30 U⋅mL(−1) of CA19-9 in blood. This is below the cutoff value (37 U mL(−1)) of CA 19-9. The assay duration for blood samples is 35 min. In our perception, the assay represents a rapid and low-cost tool for rapid determination of CA19-9 in blood that holds promise for clinical applications, particularly in limited resource settings.